La Scuola Rinnovata de Giuseppina Pizzigoni entre droits de l’enfant et changement social - Sandra Chistolini (Éducation et Socialisation)
Giuseppina Pizzigoni (1870-1947), founder of the Scuola Rinnovata Pizzigoni in Milan, is one of the greatest figures in twentieth-century Italian education. The 1907 educational plan began with a new building structure based on the experimental method, which is still in operation today. La Rinnovata was part of the new school movement and had the characteristics of an active school. The master’s ingenious idea overturned the organisation of free state schools to give all children (aged 0-14) access to education. She anticipated outdoor education and theorised the special teaching environment, rich in educational subjects. The school was a response to the social needs arising from industrialisation, urbanisation and internal migration. The malaise of childhood demanded the formation of a new social and civic conscience, a democratic culture. The Fondo Pizzigoni, the archive created within the Department of Educational Sciences at the University of Rome Tre, collects documents that bear witness to the pedagogy and method. From the perspective of ethnomethodology, we discuss the validity of the experimental method for teaching according to nature, truth and experience for an inclusive and sustainable school characterised by processes of democratic socialisation.